Mengungkap Sumber Pengetahuan: Harmoni Antara Akal, Indera, Intuisi, dan Wahyu - Dalimunte, Muhammad Fitrah (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study examines the harmony among four primary sources of knowledge—reason, senses, intuition, and revelation—in shaping human understanding of reality. Although each source has its uniqueness and limitations, this research aims to uncover how these four can complement each other to produce holistic and comprehensive knowledge. The approach used is qualitative, involving a literature analysis from various perspectives, including philosophy, religion, and modern science. The findings reveal that reason provides logical and analytical abilities, the senses serve as the primary gateway for absorbing empirical information, intuition paves the way for spontaneous and profound understanding, while revelation offers transcendental knowledge derived from divine authority. When synergized effectively, these four sources can create harmony that enriches the development of knowledge while maintaining a balance between rational, empirical, and spiritual aspects. This study recommends an integrative approach in education and research to foster more inclusive interdisciplinary collaboration rooted in ethical principles.